2021
DOI: 10.3390/nu13020646
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Unripe Banana Flour on Gut-Derived Uremic Toxins in Individuals Undergoing Peritoneal Dialysis: A Randomized, Double-Blind, Placebo-Controlled, Crossover Trial

Abstract: In chronic kidney disease (CKD), the accumulation of gut-derived metabolites, such as indoxyl sulfate (IS), p-cresyl sulfate (pCS), and indole 3-acetic acid (IAA), has been associated with the burden of the disease. In this context, prebiotics emerge as a strategy to mitigate the accumulation of such compounds, by modulating the gut microbiota and production of their metabolites. The aim of this study was to evaluate the effect of unripe banana flour (UBF—48% resistant starch, a prebiotic) on serum concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 69 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…These trials evaluated 4 different treatment agents, including probiotics, prebiotics, synbiotics, and placebo. Out of 25 studies, nine studies ( 22 , 25 , 26 , 30 , 32 , 34 , 36 , 39 , 40 ) compared prebiotics with placebo, nine studies ( 16 , 21 , 24 , 27 29 , 37 , 41 , 42 ) compared probiotics with placebo, six studies ( 15 , 20 , 23 , 33 , 35 , 38 ) compared synbiotics with placebo as well as one study ( 31 ) was three-arm RCT that compared probiotics, synbiotics and placebo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These trials evaluated 4 different treatment agents, including probiotics, prebiotics, synbiotics, and placebo. Out of 25 studies, nine studies ( 22 , 25 , 26 , 30 , 32 , 34 , 36 , 39 , 40 ) compared prebiotics with placebo, nine studies ( 16 , 21 , 24 , 27 29 , 37 , 41 , 42 ) compared probiotics with placebo, six studies ( 15 , 20 , 23 , 33 , 35 , 38 ) compared synbiotics with placebo as well as one study ( 31 ) was three-arm RCT that compared probiotics, synbiotics and placebo.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 25 studies, 15 studies ( 15 , 16 , 22 , 24 , 27 , 29 , 31 , 32 , 36 42 ) mentioned the method of random sequence generation and were rated as “low risk,” 11 articles ( 15 , 16 , 24 , 27 , 28 , 31 , 37 , 39 42 ) referred to allocation concealment, were rated as “low risk,” 16 articles ( 15 , 16 , 24 , 27 32 , 34 , 36 41 ) reported how the Blinding of participants and personnel performed, and 14 studies ( 15 , 16 , 23 , 24 , 27 , 28 , 30 32 , 36 38 , 40 , 41 ) reported the Blinding of outcome assessment. Supplementary Figures 1 , 2 summarized the all risks of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 lists the specific characteristics of the 8 studies. Since Marta et al 2020 [ 22 ] and Andrade et al 2021 [ 26 ] adopted the treatment of intervention—washout period—reintervention, it was divided into two research groups according to the treatment before and after the washout period. According to the type of CKD (dialysis or nondialysis), we divided the data into different subgroups for combined analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The basic characteristics of the 28 RCTs are summarized in Table 1 ( 7 9 , 15 , 19 – 42 ). Among them, almost all the studies were double-blinded, except for five (2 were single-blinded, 2 were open-label, and the other was triple-blinded).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that probiotics, prebiotics, and/or synbiotics are good for the treatment of CKD by modulating the immune response, improving glomerular function, and lowering serum uremic toxins and inflammatory factors. However, some other articles reached contradictory conclusions (7)(8)(9). Although a small number of studies have systematically evaluated the efficacy of probiotics, prebiotics, and synbiotics in the treatment of CKD, their conclusions are inconsistent and very different (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%